3D printed lactic acid bacteria hydrogel: cell release kinetics and stability - Yifei Liu; Xintao Yin; Xiudong Xia; Zhen Liu; Lifei Chen; Mingsheng Dong (Food Science and Human Wellness)
In this study, a new type of 3D printed living biological hydrogel was developed by integrating lactic acid bacteria (LAB) into biocompatible and non-toxic polymer materials. Interestingly, the living materials loaded with LAB can be freeze-dried and reused for more than 100 times. The bio-hydrogel can be used to co-culture different LAB and keep its fermentation performance stable in long-term use. The release kinetics model and response surface method were used to simulate and optimize the bacteria release mode in the bio-hydrogel. The results show that the release of bacteria from hydrogel is regulated by the coupling of Fickian diffusion and polymer swelling. The stability of LAB hydrogel was evaluated by reuse experiments. The images of confocal microscopy and scanning electron microscope showed that the bacteria with high cell viability were distributed in the hydrogel and intact structure of the living hydrogel was maintained after 100 times of reuse as yoghurt starter. In conclusion, the 3D printed LAB bio-hydrogel developed in this study has the advantage of reuse and sustainability, which is expected to open up a new way for the preparation of food culture starter.